Obtenção de cerâmicas à base de tricálcio fosfatos utilizando óxido de magnésio como aditivo - Carneiro, Andréa Cristine de Souza (2007)
The tricalcium phosphate ceramics has been widely investigated in the last years due its bioresorbable behavior. The limiting factor of the application of these materials as temporary implants is its low strength resistance. The tricalcium phosphate presents an allotropic transformation β→α around 1250 ºC that degrades its resistance. Some studies have been developed in order to densify this material at this temperature range. The objective of this work is to study the influence of the addition of magnesium oxide (MgO) in the sintering of β-TCP. The processing route was uniaxial hot pressing and its objective was to obtain dense samples. The samples were physically characterized through density and porosity measurements. The thermal behavior was studied through dilatometric, thermal differential and thermogravimetric analysis. The mechanical properties were characterized by three point flexure test and Vickers microhardness measurements, analyzed of the microstructure. The addition of magnesium oxide doesn t cause an improvement of the mechanical strength in relation to material without additive.